Distribution and habitat utilization of the Visayan Leopard Cat Prionailurus bengalensis rabori - Lorica, Ma. Renee P. (Banwa, 2006)
We conducted an ethnobiological survey to investigate the distribution, habitat utilization, threats and likely conservation status of the maral (Prionailurus bengalensis rabori) throughout its currently known and presumed recent range in the West Visayas faunal region. Key sites were mapped, and factors such as habitat type, distance (of non-forest habitats) from nearest forest cover, presence/absence of alternative cover, and elevation, were correlated to assess their effects. We found that these animals are not confined to forested habitats, and can be indeed persist in sugar cane cultivation areas far removed from the nearest available forest habitats, but they are associated with the presence of alternate cover, and distance from nearest forest cover has an inverse relationship to the species' presence. Based on its limited range, the very high overall extent of deforestation in this region and other factors (e.g. continued hunting pressure, changing agricultural practices, etc.), it is recommended that the subspecies be included in the Philippine List of Threatened Species and added to the IUCN Red List; the latter under the status category of Vulnerable.